2014
DOI: 10.1155/2014/350416
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between PFGE Groups andmrp/epf/slyGenotypes of HumanStreptococcus suisSerotype 2 in Northern Thailand

Abstract: Streptococcus suis infection is a severe zoonotic disease commonly found in Northern Thailand where people often consume raw pork and/or pig's blood. The most frequent clinical presentations are meningitis, sepsis, and endocarditis with higher rate of mortality and hearing loss sequelae. To clarify the correlation between pulsed-field gel electrophoresis (PFGE) groups and mrp/epf/sly genotypes of S. suis serotype 2, 62 patient and 4 healthy pig isolates from Northern Thailand were studied. By PFGE analysis, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…Moreover, most of the isolates belonging to serotypes 3 and 2 in this study showed the genotype epf − / mrp + / sly − , which is consistent with a previous report in Thailand demonstrating that 80.6% of S. suis isolates from humans were of serotype 2 with the epf − / mrp + / sly − genotype [36]. Recently, the number of human cases of S. suis infection has increased in Asia, including Korea [4, 14, 26, 36], warning of the possible transmission of S. suis from pigs to humans with regular exposure to pigs, such as those working in the pig industry. Moreover, pork is the most popular meat in Korea; therefore, even people who do not have direct contact with pigs might also be at risk of infection via consumption of insufficiently cooked pork or from contact with the raw meat during cooking [26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, most of the isolates belonging to serotypes 3 and 2 in this study showed the genotype epf − / mrp + / sly − , which is consistent with a previous report in Thailand demonstrating that 80.6% of S. suis isolates from humans were of serotype 2 with the epf − / mrp + / sly − genotype [36]. Recently, the number of human cases of S. suis infection has increased in Asia, including Korea [4, 14, 26, 36], warning of the possible transmission of S. suis from pigs to humans with regular exposure to pigs, such as those working in the pig industry. Moreover, pork is the most popular meat in Korea; therefore, even people who do not have direct contact with pigs might also be at risk of infection via consumption of insufficiently cooked pork or from contact with the raw meat during cooking [26].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies, including those using experimental pig infection models, showed that serotype 2 strains with the epf + / mrp + genotype are highly virulent to pigs [ 15 , 39 , 41 ]. Moreover, most of the isolates belonging to serotypes 3 and 2 in this study showed the genotype epf − / mrp + / sly − , which is consistent with a previous report in Thailand demonstrating that 80.6% of S. suis isolates from humans were of serotype 2 with the epf − / mrp + / sly − genotype [ 36 ]. Recently, the number of human cases of S. suis infection has increased in Asia, including Korea [ 4 , 14 , 26 , 36 ], warning of the possible transmission of S. suis from pigs to humans with regular exposure to pigs, such as those working in the pig industry.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, Mai et al [31] reported that human S. suis strains also grouped by isolation year. Similarly, Tharavichitkul et al [32] and Huang et al [33] described the tendency to cluster pulsotypes with virulence profiles, which was also observed in S. suis strains isolated from rabbits [34].…”
Section: Discussionmentioning
confidence: 68%
“…No variant phenotype of mrp was found in the isolates, whereas the epf variant ( epf *) was detected in one isolate of serotype 4. All serotype 2 isolates presented the same genotype, mrp−/epf – /sly+ , in contrast to strains isolated from humans in the same geographical region that carried the mrp + /epf − /sly − genotype (80.6%) [ 22 ]. These results indicate a difference within serotype 2; strains from humans presented only the mrp gene, while strains from pigs presented only the sly gene.…”
mentioning
confidence: 99%